Modulating excited‐state intramolecular proton transfer of 2‐(5‐(4‐carboxyphenyl)‐2‐hydroxyphenyl)benzothiazole depending on substituents: A DFT/TD‐DFT study. (20th July 2020) - Ni, Mei; Fang, Hua
Abstract: The OH‐based excited‐state intramolecular proton transfer (ESIPT) of 2‐(5‐(4‐carboxyphenyl)‐2‐hydroxyphenyl)benzothiazole (CHBT) derivatives (4R‐CHBT) that were replaced by electron‐donating groups (CH3, OH) and electron‐withdrawing groups (COOH, CF3, CN) have been studied by the time‐dependent density functional theory (TD‐DFT) method. We analyzed structural parameters, infrared (IR) vibrational spectrum, frontier molecular orbitals (FMOs), and electronic spectra, which can describe the trend of ESIPT process. The constructed potential energy surfaces showed that the ESIPT potential energy barriers of 4R‐CHBT are in the range of 0.25 to 0.62 kcal/mol, which are just a little bigger than that value of CHBT. All the chosen substituents, no matter electron‐donating or electron‐withdrawing groups, make ESIPT processes slightly more difficult. Abstract : The electron‐withdrawing group (COOH, CF3, CN) increased the ESIPT potential barrier of CHBT, while the electron‐donating group (CH3, OH) had little effect on ESIPT process. The weaker the electron‐withdrawing ability, the smaller the ESIPT potential barrier.